If host is refractory, insistent parasite goes berserk: Trypanosomatid Blastocrithidia raabei in the dock bug Coreus marginatus - Frolov, Alexander O; Malysheva, Marina N; Ganyukova, Anna I; Spodareva, Viktoria V; Králová, Jana; Yurchenko, Vyacheslav; Kostygov, Alexei Y (PloS one, 2020)
Here we characterized the development of the trypanosomatid Blastocrithidia raabei in the dock bug Coreus marginatus using light and electron microscopy. This parasite has been previously reported to occur in the host hemolymph, which is rather typical for dixenous trypanosomatids transmitted to a plant or vertebrate with insect's saliva. In addition, C. marginatus has an unusual organization of the intestine, which makes it refractory to microbial infections: two impassable segments isolate the anterior midgut portion responsible for digestion and absorption from the posterior one containing symbiotic bacteria. Our results refuted the possibility of hemolymph infection, but revealed that the refractory nature of the host provokes very aggressive behavior of the parasite and makes its life cycle more complex, reminiscent of that in some dixenous trypanosomatids. In the pre-barrier midgut portion, the epimastigotes of B. raabei attach to the epithelium and multiply similarly to regular insect trypanosomatids. However, when facing the impassable constricted region, the parasites rampage and either fiercely break through the isolating segments or attack the intestinal epithelium in front of the barrier. The cells of the latter group pass to the basal lamina and accumulate there, causing degradation of the epitheliocytes and thus helping the epimastigotes of the former group to advance posteriorly. In the symbiont-containing post-barrier midgut segment, the parasites either attach to bacterial cells and produce cyst-like amastigotes (CLAs) or infect enterocytes. In the rectum, all epimastigotes attach either to the cuticular lining or to each other and form CLAs. We argue that in addition to the specialized life cycle B. raabei possesses functional cell enhancements important either for the successful passage through the intestinal barriers (enlarged rostrum and well-developed Golgi complex) or as food reserves (vacuoles in the posterior end).
Keywords: Host-Parasite Interactions; Life Cycle Stages; Trypanosomatina; Euglenozoa Infections; Hemolymph; infekce prvoky kmene Euglenozoa; Animals; stadia vývoje; Intestinal Mucosa; elektronová mikroskopie; Microscopy, Electron; Disease Resistance; střevní sliznice; zvířata; Heteroptera; odolnost vůči nemocem; hemolymfa; interakce hostitele a parazita